Numerical study of heat and mass transfer in MHD flow of nanofluid in a porous medium with Soret and Dufour effects. Issue 5 (31st January 2021) - Qureshi, Imran Haider; Nawaz, M.; Abdel‐Sattar, M. A.; Aly, Shaban; Awais, M.
Abstract: This article models the transport mechanism of mass and heat energy under temperature and concentration gradients. Mathematical models in the form of partial differential equations based on conservation laws for fluid flow and transfer of heat and mass subjected to thermal diffusion and diffusion thermos, heat generation porous medium, and buoyancy forces are developed under boundary layer approximations. These models along with models of nanostructures are solved numerically using the shooting method with the Runge–Kutta method of order five. Convergent solutions are obtained and are used for parametric analysis regarding thermal enhancement of a working fluid having nanoparticles of CuO, Al2 O3, and TiO2 . Numerical experiments are performed and it is observed that the transport of heat is accelerated when the compositional gradient is increased. Similarly, a significant rise in the transport across concentration is noted when the temperature gradient is increased. The magnetohydrodynamic flow experienced retardation when the porous medium parameter and Hartmann number are increased. The temperature increased when the friction force produced heat and that heat is distributed to the particles of the fluid. Hence, viscous dissipation is responsible for widening the thermal boundary layer region.